PENYALAHGUNAAN WEWENANG OLEH PEJABAT PEMERINTAHAN DALAM PERSPEKTIF UNDANG-UNDANG ADMINISTRASI PEMERINTAHAN - Wellem Hendra Balubun; Billy Andre Tohatta (Fakultas Hukum, Universitas Caritas Indonesia, 2026)
The abuse of authority by government officials is an issue that potentially hinders the realization of good governance and the principles of the rule of law. In the conduct of government affairs, officials are granted authority to perform functions related to public service, development, and the regulation of societal life. However, the exercise of authority in a manner inconsistent with the purpose for which it was granted can lead to irregularities that harm both the public and the state. This research aims to analyze the concepts and forms of abuse of authority under Law Number 30 of 2014 concerning Government Administration; to examine the role of discretion and the General Principles of Good Governance in preventing such abuse; and to analyze state administrative oversight mechanisms for controlling and addressing the abuse of authority by government officials. The study employs a normative legal research method utilizing statutory, conceptual, and case-based approaches. Legal materials were gathered from legislation, books, scholarly journals, court rulings, and relevant administrative law doctrines. A qualitative analysis was conducted using a descriptive-analytical method. The findings indicate that, under the Government Administration Law, the abuse of authority encompasses acts of exceeding authority, mixing authorities, and acting arbitrarily. Discretion plays a crucial role as an instrument to ensure effective governance; however, its exercise must be constrained by the AUPB to prevent it from devolving into an abuse of authority. Furthermore, state administrative oversight—comprising internal supervision, external supervision, and judicial review by the State Administrative Court—plays a strategic role in preventing and addressing the abuse of authority. Consequently, strengthening oversight systems and implementing the principles of good governance are vital factors in realizing a government that is accountable, transparent, and oriented toward the public interest.